Customers’ perceptions of the importance of characteristic in service organisations - Ali, Mass Hareeza (2010)
This research focuses on the importance of characteristic in service organizations in Malaysia. The customers perceptions towards the bank, Telekom and the Univeristy are presented in the form of data gathered through questionnaire. The SERVQUAL instrument was developed with seven requirement dimension of service quality: performance, responsiveness, credibility, reliability, courtesy tangibles and features. This study will analyse the importance of characteristic according to the dimension and the ‘assessment of specific requirements’ also being studied in the participated service organizations. Results from the research were expected to contribute new information in the development criteria and action should be taken by the management of the service organizations.